Characterization of Bradyrhizobium spp. Nodulating Lupinus cosentinii and L. luteus Microsymbionts in Morocco - Missbah El Idrissi, Mustapha; Bouhnik, Omar; ElFaik, Salma; Alami, Soufiane; Lamin, Hanane; Bedmar, Eulogio J.; Abdelmoumen, Hanaa (Frontiers in Agronomy, 2021)
In this work, we analyzed the diversity of the nodule-forming bacteria associated with Lupinus luteus and L. cosentinii grown in the Maamora Cork oak forest acidic soils, in Morocco. The phenotypic analysis showed the high diversity of the strains nodulating the two lupine’s species. The strains were not tolerant to acidity or high alkalinity. They don’t tolerate salinity or high temperatures either. The strains isolated from L. luteus were more tolerant to antibiotics and salinity than those isolated from L. cosentinii. The plant growth-promoting (PGP) activities of our strains are modest, as, among the 28 tested isolates, only six produced auxins; six produced siderophores, whereas three solubilized phosphates. Only two strains possess the three activities. The rrs gene sequences from eight representative strains selected following ARDRA and REP-PCR results revealed they were members of the genus Bradyrhizobium. Six strains were then retained for further molecular analysis. The glnII, recA, gyrB, dnaK, and rpoB housekeeping genes sequences phylogeny showed that some strains were close B. lupini LMG28514T whereas others may constitute new genospecies in the genus Bradyrhizobium The strains were unable to nodulate Glycine max and Phaseolus vulgaris and effectively nodulated L. luteus, L. cosentinii, L. angustifolius, Chamaecytisus albidus and Retama monosperma. The nodC and nodA symbiotic genes phylogenies showed that the strains are members of the genistearum symbiovar.